1999
DOI: 10.1046/j.1365-2796.1999.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

The health care costs of heart failure in Sweden

Abstract: Abstract. Ryde Ân-Bergsten T, Andersson F (AstraZeneca R&D, Lund; and AstraZeneca R&D, Mo Èlndal; Sweden). The health care costs of heart failure in Sweden. J Intern Med 1999; 246: 275±284.Aim. Heart failure is a common and serious condition requiring extensive health care resources. The aim of this study is to estimate the total treatment costs of heart failure in Sweden.Methods and results. The study is a prevalencebased cost-of-illness study. It includes costs of institutional care (hospitals and nursing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
96
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 33 publications
7
96
0
4
Order By: Relevance
“…In Sweden, heart failure is the most frequent discharge diagnosis within internal medicine (Mejhert et al, 2001). Because of the high rates of hospitalizations, the care of patients with CHF accounts for 1-2% of the total health expenditure in Sweden (Ryden-Bergsten & Andersson, 1999).…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…In Sweden, heart failure is the most frequent discharge diagnosis within internal medicine (Mejhert et al, 2001). Because of the high rates of hospitalizations, the care of patients with CHF accounts for 1-2% of the total health expenditure in Sweden (Ryden-Bergsten & Andersson, 1999).…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…Heart failure is a rapidly increasing CVD condition and a major cause for hospitalisation, with costs comprising 1-2% of the total health budget in many developed countries [7,8]. A recent meta-analysis of clinical trials, including 4-5 years of follow-up, demonstrated that intensive glycaemic control did not prevent heart failure in type 2 diabetes [9].…”
Section: Introductionmentioning
confidence: 99%
“…For many industrialized countries, the prevalence of heart failure (HF) approaches 1-4% of the population and medical expenditures have been estimated at 1-5% of health care spending in some settings [1][2][3][4][5][6][7]. Mortality at 30 days and 1 year after the initial diagnosis of HF increases with advanced age and co-morbidity, and current estimates are 7% and 18% for younger patients to 18% and 60% for older patients with higher co-morbidity [5,6,[8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%